2012
DOI: 10.1039/c2cc36236h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon oxidation catalyzed by self-folded metal-coordinated cavitands

Abstract: Functionalized cavitands have been shown to self-fold via coordination of Fe(II) salts and effect catalytic C-H oxidation reactions of unfunctionalized alkanes under mild aqueous conditions in the presence of tert-butyl hydroperoxide as co-oxidant. Secondary and tertiary C-H bonds can be converted to ketones and alcohols, respectively, and ethers can be converted to esters. The cavitands retain the catalytic metal throughout the reaction, and can be recovered by filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Taking into consideration the ability of mononuclear iron sites to mediate oxidation reactions in a selective manner, several families of bioinspired mononuclear nonheme iron complexes have been developed and tested during the past decade in the challenging oxidation of C–H and CC bonds. Selected families are capable of eliciting enzyme-like reactivity, meaning that they can mediate oxidations through metal-centered processes without a significant involvement of free diffusing radicals. , Such studies have shown that the activity of these complexes as oxidation catalysts depends, in a very delicate manner, on a number of aspects. Some of them are rather obvious such as metal nuclearity, ligand denticity, strength of metal binding, presence of available coordination sites, nature of the ligand donor set, or the oxidatively robust nature of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the ability of mononuclear iron sites to mediate oxidation reactions in a selective manner, several families of bioinspired mononuclear nonheme iron complexes have been developed and tested during the past decade in the challenging oxidation of C–H and CC bonds. Selected families are capable of eliciting enzyme-like reactivity, meaning that they can mediate oxidations through metal-centered processes without a significant involvement of free diffusing radicals. , Such studies have shown that the activity of these complexes as oxidation catalysts depends, in a very delicate manner, on a number of aspects. Some of them are rather obvious such as metal nuclearity, ligand denticity, strength of metal binding, presence of available coordination sites, nature of the ligand donor set, or the oxidatively robust nature of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…'Click' chemistry and saponification with Cs 2 CO 3 gave cavitands 28b, 29b, and 30b. 40 For example, in the presence of the complex, fluorene 31 was smoothly converted to fluorenone 32 under mild conditions (Scheme 10). However, upon sonication at ambient temperature with Cu(CH 3 CN) 4 BF 4 , all cavitands (28)(29)(30) formed the corresponding copper complexes.…”
Section: Modifications At the Upper And Lower Rimsmentioning
confidence: 99%
“…It is also noteworthy that the N 1s XPS trace for the unbound 2·Fe catalyst is much more complex than those from the 2·Fe·SBA-15 tethered catalyst, suggesting perhaps more than one bonding mode for the iron ion in the former case. Fe bonding to the cavitand seems simpler on the tethered cavitand; in solution, two coordination modes were observed for 1·Fe , with either one or two Fe(II) ions …”
mentioning
confidence: 99%
“…Here, we report on the performance of a heterogeneous catalyst made by tethering an iron-coordinated cavitand catalyst previously developed in our laboratory , to a SBA-15 mesoporous solid. Cavitands have been shown to coordinate Fe(II) ions, allowing solution-phase C–H oxidation of unactivated hydrocarbons in mild, aqueous conditions. , They are also well suited for use as solid surface-mounted scaffolds.…”
mentioning
confidence: 99%
See 1 more Smart Citation